Could Complete Blood Count Parameters and Non-fasting Cholesterol Profile Describe Inflammation and Oxidative Stress in Chronic Kidney Disease? - Ika Nindya Kadariswantiningsih; Mochammad Thaha; Cahyo Wibisono Nugroho; Berliana Hamidah; Haerani Rasyid; Zaky El Hakim; Maulana Muhtadin Suryansyah; Mohammad Yusuf Alsagaff; Djoko Santoso; Maulana Antiyan Empitu; Yusuke Suzuki (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Establishment of inexpensive clinical laboratory tests to evaluate inflammation and oxidative stress is urgently needed in the limited resources settings. This study aims to investigate the potential of complete blood count (CBC) parameters and non-fasting cholesterol profile parameters to describe inflammation and oxidative stress in chronic kidney disease (CKD) patients.METHODS: Measurement of CBC, non-fasting cholesterol profile, high sensitivity C-reactive protein (hs-CRP) and malondialdehyde (MDA) were performed in 71 CKD patients grouped into hemodialysis (HD) and non-hemodialysis (non-HD). Correlation analysis were performed to assess the potential of CBC and cholesterol profile to describe the level of hs-CRP and MDA.RESULTS: In the HD group, total cholesterol was moderately associated with hs-CRP while total cholesterol/HDL-C ratio, monocyte/HDL-C ratio, monocyte/LDL-C ratio, neutrophil/HDL-C ratio, neutrophil/LDL-C ratio, platelet/HDL-C ratio and platelet/LDL-C ratio were strongly associated with hs-CRP. In the non-HD group,only neutrophil/total cholesterol ratio and platelet/total cholesterol ratio that were associated with hs-CRP. Total cholesterol, monocyte/LDL-C ratio, neutrophil/LDL-C ratio and platelet/LDL-C ratio were moderately associated with MDA while total cholesterol/HDL-C ratio, monocyte/HDL-C ratio, neutrophil/HDL-C ratio and platelet/HDL-C ratio were strongly associated respectively with MDA in HD group. In the non-HD group, total cholesterol/HDL-C ratio, neutrophil/HDL-C ratio and platelet/HDL-C ratio were moderately associated with MDA in non-HD group while monocyte/HDL-C ratio was weakly associated with MDA.CONCLUSION: Some CBC parameters and non-fasting cholesterol profile such as cholesterol/HDL-C, monocyte/HDL-C, neutrophil/HDL-C and platelet/HDL-C ratio showed a potential to describe the inflammation and stress oxidative markers, given some strong associations with the level of hs-CRP and MDA. Further study is needed to assess whether this parameter represent long-term prognostic value among CKD patients.KEYWORDS: inflammation, oxidative stress, CRP, MDA, TAC, 8-OHdG, CBC, cholesterol